Refomulasi Epistemologi Hijrah dalam Dakwah - Aswadi Aswadi (Islamica: Jurnal Studi Keislaman, 2011)
The paper discusess the idea of Hijrah and its historic role in the process of Islamic propagation (da?wah). Hijrah is a physical migration from Mekkah to Medinah; a migration that has implied both religious and spiritual transofrmation. In its literal meaning, Hijrah is simply to move from one place to another. In the history of da?wah, Hijrah is a moment in which Islam underwent a process of change and transition from one situation into another. Hijrah was the first stepping stone toward the more vibrant and active propagation of Islam. The paper deals with this notion of Hijrah as the strategic move toward the successful mission of disseminating Islam. These issues together with the many implications that Hijrah has will be the focus of this paper. The paper argues that Hijrah is not simply to make a physical movement from one place to another. It is also about the spiritual and religious transformation of the Muslim ummah. Through Hijrah a new social, political and cultural order is resurrected. To make our discussion more lively, the paper will refer to many Qur?anic verses and prophetic traditions that speak of Hijrah and interpret them in the light of the historic Hijrah. Hence, we look at Hijrah as not only an event in history, but also a norm of religion that has a spiritual value of its own.